The Perspectives of Parents of Primary School Students in the City of Amman about their Children’s Use of the Moodle and the Obstacles they faced while using it - Ajlouni, Khalid Ibrahim; Ameerah, Amani Mohammed Ahmad (Journal of Curriculum and Teaching Methodology, 2023)
This study aims to reveal the perspectives of parents of primary school students about their children’s use of Moodle learning management system, the obstacles they face while using it, and the degree to which primary school students use the learning management system from the point of view of their parents, where the researchers used the descriptive survey approach. To answer the questions of the study, researchers distributing the questionnaire to the study sample of (384) parents, the questionnaire was consisted of three basic sections, firstly: it includes demographic information, secondly: the perspectives of parents of primary school students regarding their children’s use of the Moodle, and lastly: the perspectives of parents on the obstacles they are facing during distance learning, in addition to, an interview was also conducted with (16) participants from parents. The results of the study showed that the degree of satisfaction of parents of primary school students with the use of the Moodle in education was a medium degree (3.19), and the mean degree of the obstacles faced by primary school students while using the Moodle in education from the point of view of their parents was (3.73). This study recommended that the looking at the age side of students, training and educating them on the importance of distance education, and encouraging the use of e-learning management systems with their multiple capabilities because of its many benefits that serve the educational process, and also recommended the further studies in this regard.
Keywords: Moodle E-Learning Management Systems; Parents of Primary Students; Private Schools in Amman